The Ways to Optimize Costs of Enterprise on the Example of PJSC «Ukrainian Railways» - Nagorna Iryna V. (Bìznes Inform, 2020)
The article is aimed at finding ways to optimize costs at the production subdivision «Operational wagon depot Kupyansk» of the Regional division «Southern Railway» of the Private Joint Stock Company «Ukrainian Railways» on the basis of the performed analysis of the composition and structure of costs, profitability, the impact of the amount of costs on performance indicators, the level of costs per 1 UAH of the consummated services, and operational analysis. The views of scholars on the term «costs» are explored. It is defined that cost management is quite a complex and important process in the course of carrying out economic activity along with determining the quality of further results of enterprise. The main methodological bases of cost management, economic condition of the enterprise are researched. Optimization measures for further development of the enterprise are proposed, which will allow to use its resources more efficiently, to achieve an increase sales and maximize profits. The authors provide recommendations on managing the enterprise costs in order to stimulate the growth of competitiveness. The focus is placed on the mechanism of minimizing the costs of the enterprise in the total amount of net income, because efficient use of costs can not be carried out without structural changes in the sphere of their management. It is identified that cost management is an interconnected complex of works, which forms and influences the behavior of costs during economic activity, as well as is aimed at achieving the optimal level of costs. The proposed measures as to optimizing costs can be used by directors and managers of the enterprise to make informed decisions on the prospective development of the enterprise.